2020
DOI: 10.1126/scitranslmed.aba0769
|View full text |Cite
|
Sign up to set email alerts
|

Chemical perturbations reveal that RUVBL2 regulates the circadian phase in mammals

Abstract: Transcriptional regulation lies at the core of the circadian clockwork, but how the clock-related transcription machinery controls the circadian phase is not understood. Here, we show both in human cells and in mice that RuvB-like ATPase 2 (RUVBL2) interacts with other known clock proteins on chromatin to regulate the circadian phase. Pharmacological perturbation of RUVBL2 with the adenosine analog compound cordycepin resulted in a rapid-onset 12-hour clock phase-shift phenotype at human cell, mouse tissue, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 60 publications
1
13
0
Order By: Relevance
“…Since clock gene transcript abundance was measured in heads 20 , and the vast majority of clock gene expression in heads is from photoreceptors 56 , such differential use of NIPPED-A in the Tip60 and SAGA complexes could result from tissue-specific interactions with CLK-CYC complexes. Our data strongly support an interaction between NIPPED-A and the CLK-CYC complex, consistent with recent work showing that mammalian TRRAP is present in CLOCK-BMAL1 complexes in mice 7 . Thus, our results suggest that interactions between NIPPED-A and CLK-CYC promote histone modifications via the SAGA and Tip60 complexes, thereby translating CLK-CYC binding into target gene transcription.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Since clock gene transcript abundance was measured in heads 20 , and the vast majority of clock gene expression in heads is from photoreceptors 56 , such differential use of NIPPED-A in the Tip60 and SAGA complexes could result from tissue-specific interactions with CLK-CYC complexes. Our data strongly support an interaction between NIPPED-A and the CLK-CYC complex, consistent with recent work showing that mammalian TRRAP is present in CLOCK-BMAL1 complexes in mice 7 . Thus, our results suggest that interactions between NIPPED-A and CLK-CYC promote histone modifications via the SAGA and Tip60 complexes, thereby translating CLK-CYC binding into target gene transcription.…”
Section: Discussionsupporting
confidence: 92%
“…6 Significantly longer than w 1118 , UAS-dcr; + / + ; pdf-Gal4/ + control flies (p < 0.05). 7 Significantly lower power than w 1118 , UAS-dcr; tim-Gal4/ + ; + / + control flies (p < 0.05). 8 Significantly lower power than w 1118 , UAS-dcr; + / + ; pdf-Gal4/ + control flies (p < 10 -2 ).…”
Section: Nipped-a Associates With Clk-cyc and Influences Circadian Pementioning
confidence: 94%
See 1 more Smart Citation
“…Chemical screens to identify small molecules directly targeting the circadian phase will be the potential therapeutic approach. Recently, a paper authored by Ju et al reported that a natural compound, cordycepin, dramatically induces "type 0" phase shifts in mammalian cells and animals [3], while its clinical relevance needs further evaluation. Third, although we live in and follow the same solar/social time‐schedule, each individual person has a unique chronotype for his/her own.…”
Section: Circadian Phase a Key Point For Chronotherapymentioning
confidence: 99%
“…RUVBL2 binds RPAP3 and PIH1D1, two subunits of the R2TP complex, functions not shared by RUVBL1. Interestingly, cordycepin, a derivative of the nucleoside adenosine affects the circadian clock in mammals by targeting RUVBL2 (Ju et al, 2020). A crystal structure of RUVBL1-RUVBL2 bound to cordycepin (PDB 6K0R) shows that the compound interacted with all RUVBL2 subunits but not with RUVBL1 and the N-termini of RUVBL2 were visible and folded into the protein.…”
Section: Discussionmentioning
confidence: 99%